BioMedicine - SpringerLink (Online service) (Taichung : China Medical University : Imprint: China Medical University.)
BioMedicine aims to publish high quality scientific research in the field of translational and personalized medicine, with the goal of promoting and disseminating medical science knowledge to improve global health.
Keywords: Medicine; Medicine/Public Health, general